Infrastructure and Economic Growth in Asia - Cockburn, John.; Dissou, Yazid; Duclos, Jean-Yves.; Tiberti, Luca.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2013)
Public spending on infrastructure plays an important role in promoting economic growth and poverty alleviation. Empirical studies unequivocally show that under-investment in infrastructure limits economic growth. At the same time, numerous other studies have shown that investment in infrastructure can be an effective tool in fighting poverty reduction. In that context, the financing of infrastructure has been a critical element of most economic growth and poverty reduction strategies in developing countries since the start of this millennium. This book provides a comparative analysis of the aggregate and sectoral implications of higher spending on infrastructure in three very different Asian countries: China, Pakistan, and the Philippines. Particular attention is paid to the role of alternative financing mechanisms for increasing public infrastructure investment, namely distortionary and non-distortionary means of financing. The book will be of interest to scholars and policy-makers concerned with economic growth in developing countries.
Introduction -- Infrastructure and Growth -- Approach -- China -- Pakistan -- Philippines -- Summary and conclusion.
Keywords: Economics; Development Economics; Endogenous growth (Economics).; Finance; Economics/Management Science; Development Economics; Economic Growth; Public Finance & Economics